2019
DOI: 10.1371/journal.ppat.1007843
|View full text |Cite
|
Sign up to set email alerts
|

Identification of murine gammaherpesvirus 68 miRNA-mRNA hybrids reveals miRNA target conservation among gammaherpesviruses including host translation and protein modification machinery

Abstract: Gammaherpesviruses, including the human pathogens Epstein-Barr virus (EBV) and Kaposi’s sarcoma-associated herpesvirus (KSHV), establish lifelong latent infection in B cells and are associated with a variety of tumors. In addition to protein coding genes, these viruses encode numerous microRNAs (miRNAs) within their genomes. While putative host targets of EBV and KSHV miRNAs have been previously identified, the specific functions of these miRNAs during in vivo infection are largely unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…To determine whether enhanced representation of viral miRNAs in RISC is a conserved feature of γHVs, we supplemented data from our previously published KSHV[ 42 ] and MHV68[ 66 ] qCLASH studies with small RNA sequencing to similarly compare KSHV and MHV68 hybrid levels to their respective miRNA expression. Similar to our findings with in vitro EBV miRNA expression, KSHV miRNAs were found to be expressed at low levels in KSHV infected LTC-TIVE cells ( S8A Fig ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether enhanced representation of viral miRNAs in RISC is a conserved feature of γHVs, we supplemented data from our previously published KSHV[ 42 ] and MHV68[ 66 ] qCLASH studies with small RNA sequencing to similarly compare KSHV and MHV68 hybrid levels to their respective miRNA expression. Similar to our findings with in vitro EBV miRNA expression, KSHV miRNAs were found to be expressed at low levels in KSHV infected LTC-TIVE cells ( S8A Fig ).…”
Section: Resultsmentioning
confidence: 99%
“… Raw CLASH sequencing reads were obtained for KSHV infected TIVE-EX-LTC[ 42 ] (SRA accessions: SRR5876950-SRR5876952) and MHV68 infected HE2.1[ 66 ] (SRA accessions: SRR8395245-SRR8395247) cell lines, with small fraction sequencing performed on the same cell lines. (A-B; left) Yellow triangles display total viral microRNA expression, ; green triangles represent the percent of all microRNA-mRNA hybrids containing a viral microRNA, .…”
Section: Supporting Informationmentioning
confidence: 99%
“…To determine whether enhanced representation of viral miRNAs in RISC is a conserved feature of γ HVs, we supplemented data from our previously published KSHV(42) and MHV68(65) qCLASH studies with small RNA sequencing to similarly compare KSHV and MHV68 hybrid levels to their respective miRNA expression. Similar to our findings with in vitro EBV miRNA expression, KSHV miRNAs were found to be expressed at low levels in KSHV infected LTC-TIVE cells ( Figure S7A ).…”
Section: Resultsmentioning
confidence: 99%
“…The TMERs are dispensable for lytic replication and establishment of latency; however, these transcripts are required for pathogenesis during acute infection of an immunocompromised host (7,24,25). The TMERs contain bi-functional elements with a tRNA-like structure at the 5' end and hairpins that are processed into biologically-active miRNAs (7), capable of targeting a number of RNAs for post-transcriptional regulation (26). Our lab has previously shown that the tRNA-like on May 10, 2021 by guest http://jvi.asm.org/ Downloaded from γHV68 infection activates pol III promoters 5 structure is sufficient to rescue pathogenesis of a TMER deficient viral recombinant, suggesting that like the EBERs, the TMERs may contribute to pathogenesis through their interactions with host proteins (25).…”
Section: Introductionmentioning
confidence: 99%